ANALYSIS OF INFORMATION SYSTEM SUCCESS MODEL IN THE IMPLEMENTATION OF SISKEUDES 2.0 - Sarumaha, Sylvia; Maksum, Irfan Ridwan (stiatabalong.ac.id, 2021)
The presence of the village was emphasized through Law Number 6 of 2014 about Villages, village funds as a form of creation for the 3rd Nawacita so that the village government had the authority to regulate its territory. The great nominal village funds must be managed properly however in practice there is still misuse of village funds. Village Financial System (SISKEUDES) 2.0 is an application developed to improve quality village financial governance. Through analyzing the Information System Success model in SISKEUDES 2.0 it must be known that things affect the system implementation and based on observations there are factors that influence it such leadership, commitment, communication, human resources, and training. Keywords: Information System Success Model, Village Government, Village Financial System